Implementation of The Principle of Balance Between Lenders and Peer To Peer (P2p) Lending Companies: Contract Analysis of Electronic Loan Distribution At PT. Pintar Inovasi Digital (Asetku) - Martin, Christopher (Mahadi: Indonesia Journal of Law, 2023)
Peer To Peer (P2P) Lending is the result of the development of digital technology which is a solution for people who need funds quickly without having to go through convoluted procedures such as banking institutions. In P2P lending activities, there are several parties, namely Lenders, Organizing Companies, and Borrowers who are related to law. Based on POJK Number 77/POJK.01/2016 concerning Information Technology-Based Borrowing and Borrowing Services, in P2P Lending there are two kinds of legal relationships, one of which is the legal relationship between the Lender and the P2P Lending Company as outlined in the Electronic Loan Distribution Contract. In making the contract, the application of the principle of balance is important in order to create balance for the parties to the contract. This research uses a descriptive normative legal research method. Secondary data in the form of primary, secondary and tertiary legal materials were collected using library research techniques. Data analysis was performed using qualitative data analysis methods. The study results shows that the Electronic Loan Distribution Contract Number PPP/PID/2021/07/Lending Transaction TD29585580030360 between Lenders and P2P lending companies does not fulfill the overall balance principle. It was found after looking at the three aspects used as test factors for the application of the principle of balance in the form of the actions of the parties, the contents of the contract, and the execution of the contract. The principle of balance is met in the first (actions of the parties) and third (execution of the contract) aspects. Regarding the second aspect, namely the contents of the contract, the author finds that the principle of balance has not been fully implemented, because the contract is in a standard form made unilaterally by a P2P lending company for Lenders. Failure to apply the principle of balance in a contract can result in the contract becoming null and voidable or null and void.